Development of a murine iliac arteriovenous fistula model for examination of hemodialysis access-related limb pathophysiology - Kyoungrae Kim, PhD; Erik M. Anderson, MD; Andrew J. Martin, MD; Qiongyao Hu, BS; Tomas A. Cort, BS; Kenneth C. Harland, BS; Kerri A. O'Malley, PhD; Guanyi Lu, MD, PhD; Scott A. Berceli, MD, PhD; Terence E. Ryan, PhD; Salvatore T. Scali, MD (JVS - Vascular Science, 2021)
Objective: Hemodialysis access-related hand dysfunction is a common clinical feature of patients with chronic kidney disease (CKD) after arteriovenous fistula (AVF) placement. The heterogeneity in symptoms and the lack of a predictive association with changes in hemodynamic alterations precipitated by the AVF suggest that other factors are involved in the mechanisms responsible for causing hand and limb dysfunction postoperatively. To the best of our knowledge, no suitable animal models have provided a platform for performing preclinical experiments designed to elucidate the biologic drivers of access-related hand dysfunction. Therefore, our objective was to develop a novel murine AVF model that could be used to study dialysis access-related limb dysfunction. Methods: Male 8-week-old C57BL/6J mice (n = 15/group) were exposed to either an adenine-supplemented diet to induce CKD or casein-based chow (control). Four weeks after the diet intervention, the mice were randomly assigned to receive an iliac AVF (n = 10/group) or sham surgery (n = 5/group) on the left hindlimb. The mice were sacrificed 2 weeks after surgery, and AVF specimens and hindlimb skeletal muscles were collected for further analysis. Results: Before AVF or sham surgery, the glomerular filtration rates were significantly reduced and the blood urea nitrogen levels were significantly elevated in the CKD groups compared with the controls (P < .05). AVF surgery was associated with an ∼80% patency rate among the survivors (four control and three CKD mice died postoperatively). Patency was verified by changes in hemodynamics using Doppler ultrasound imaging and altered histologic morphology. Compared with sham surgery, AVF surgery reduced ipsilateral hindlimb perfusion to the tibialis anterior muscle (20%-40%) and paw (40%-50%), which remained stable until euthanasia. Analysis of gastrocnemius muscle mitochondrial respiratory function uncovered a significant decrease (40%-50%) in mitochondrial function in the AVF mice. No changes were found in the muscle mass, myofiber cross-sectional area, or centrally nucleated fiber proportion in the extensor digitorum longus and soleus muscles between the sham and AVF mice. Conclusions: The results from the present study have demonstrated that iliac AVF formation is a practical animal model that facilitates examination of hemodialysis access-related limb dysfunction. AVF surgery produced the expected hemodynamic changes, and evaluation of the limb muscle revealed a substantial mitochondrial impairment that was present without changes in muscle size. : Clinical Relevance: Autogenous arteriovenous fistula creation remains the preferred vascular access option for patients requiring chronic hemodialysis therapy. However, access-related hand dysfunction (ARHD) remains highly prevalent in this population. Clinical management of the disability is difficult because of symptom heterogeneity and limited treatment options. Additionally, the current preclinical models do not adequately replicate the pathologic condition to allow for investigation of underlying mechanisms and to test new therapies. Therefore, medical progress has been marginal. In the present study, we have outlined a novel murine model to study ARHD and described the associated mitochondrial impairments, providing a unique tool for preclinical therapeutic development.